الرعاية التأهيلية والصحية ودورها في تنمية الوعي الصحي من منظور الخدمة الاجتماعية - النصار، نزار عبدالسادة (جامعة واسط - كلية الآداب, 2024)
عادة ما نفكر بالصحة من حيث ما نفعله بأجسامنا، كمقدار التمارين الرياضية التي نقوم بممارستها والغذاء الذي نأكله، وكيفية الوقاية من مسببات الأمراض، ولكن المجموعة الاجتماعية التي ننتمي إليها ومدى سيطرتنا على حياتنا يؤثران في صحتنا أيضا. وتعد الرعاية الصحية ضرورة أساسية وملحة، بل إنها عنصر لا غنى عنه لبقاء وتنمية الإنسان والاستمتاع بالحياة، وفي العصر الحديث أصبح النظر إلى الرعاية الصحية على إنها حق لكل إنسان ومن ثم فأنها تستمد شرعيتها من حقيقة إنها تشبع احدى الحاجات الأساسية للفرد. ومن ثم فأن نجاح أي جهد تنموي يعتمد بالدرجة الأساس على سلامة الإنسان الجسمية والنفسية والعقلية واستثمار ذلك من اجل تحقيق التنمية والأمن الصحي. ومن هنا أصبح لزاما على الدول والمؤسسات الصحية من دعم برامج الرعاية الصحية لكافة أفراد المجتمع، وتوفير جميع الخدمات الصحية، خاصة للفئات الضعيفة وغير القادرة على تحمل التكاليف المادية. We usually think about health in terms of what we do with our bodies, such as the amount of exercise we do, the food we eat, and how to prevent pathogens, but the social group we belong to and how much control we have over our lives also affect our health. Health care is considered a basic and urgent necessity, it is an indispensable element for the survival and development of Man and the enjoyment of life, and in modern times, health care has become viewed as the right of every human being and therefore it derives its legitimacy from the fact that it satisfies one of the basic needs of the individual. Therefore, the success of any development effort depends primarily on the physical, psychological and mental well-being of the human being and investing this in order to achieve development and health security. Therefore, it has become an obligation for states and health institutions to support health care programs for all members of society, and provide all health services, especially for vulnerable groups and those unable to afford the material costs.
Keywords: العناية الصحية -- الوعي الصحي -- المنظور الاجتماعي